The Impact Of Edc's Marketing, Service, And Infrastructure Strategies On The Growth Of Savings Deposits At Bank Rakyat Indonesia Surabaya Pahlawan Branch - Wike Dwi Septianingrum; Fitri Ismiyanti (Publikasi Indonesia, 2023)
Banking strategy requires fast and instant service to provide